Randomized placebo-controlled study of the memory effects of pomegranate juice in middle-aged and older adults - Siddarth, Prabha; Li, Zhaoping; Miller, Karen J; Ercoli, Linda M; Merril, David A; Henning, Susanne M; Heber, David; Small, Gary W (The American journal of clinical nutrition, 2020)
Antioxidant nutrients such as the polyphenols in pomegranate juice may prevent neuronal damage from the free radicals produced during normal metabolism. Previous research in animals and a short-term clinical trial in middle-aged and older adults support the potential memory benefits of pomegranate juice; however, the long-term effects of pomegranate juice consumption on cognition have not been studied. In this study, we investigated the long-term effect of pomegranate juice on memory in nondemented middle-aged and older adults. We performed a 12-month, randomized, double-blind, placebo-controlled trial of pomegranate juice in middle-aged and older adults. Two hundred and sixty-one subjects (aged 50–75 y) were randomly assigned to consume pomegranate juice [8 oz (236.5 mL) per day] or a placebo drink (8 oz, matched constituents of pomegranate juice except for pomegranate polyphenols). Memory measures [Brief Visuospatial Memory Test-Revised (BVMT-R) and Buschke Selective Reminding Test (SRT)] were assessed at 6 and 12 mo and analyzed using a mixed-effects general linear model. Twenty-eight subjects in the pomegranate juice group and 33 subjects in the placebo group dropped out before completing the study. Baseline variables in the 98 pomegranate juice and 102 placebo group subjects who completed the study did not differ significantly. Group by time interaction was statistically significant for BVMT-R Learning (F[2, 257]= 5.90, P = 0.003; between-group effect size [ES] = 0.45): the change within the pomegranate group was not significant (ES = 0.15), whereas the placebo group showed a significant decline (ES = −0.35). Changes in the other BVMT-R scores as well as the SRT measures were not significantly different between groups. Daily consumption of pomegranate juice may stabilize the ability to learn visual information over a 12-mo period. This trial was registered at clinicaltrials.gov as NCT02093130.